Online learning drawbacks during the Covid-19 pandemic: A psychological perspective - Syahputri, Veni Nella; Rahma, Endah Anisa; Setiyana, Rusma; Diana, Sari; Parlindungan, Firman (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2020)
This study aimed at finding out the psychological effects that have been drawn by the implementation of online learning during the Covid-19 pandemic on university students. The approach implemented in carrying out this study was a descriptive qualitative approach. There were 140 students involved as respondents. The instrument used was a questionnaire set that was generated from Wiles (2020). Before proceeding with data collection process, the validity of the instrument was checked, and the items were valid. Then, the data were analyzed using Interactive Analysis as suggested by Miles, Huberman, and Saldana (2014). The result shows that from the seven mental effects raised from increased screen time, the students admit that they most likely feel fatigued (100%), they experience physical pain such as headache, shoulder sore, eyesore, and others (100%), they have bad time management (98.6%), they feel isolation being drawn from their classmates (68.6%), and they experienced uncertainty about the lecturer’s explanation during the online classes. Hence, it is suggested that there is a special unit to care about the students’ mental health during online learning in this pandemic.